2012
DOI: 10.1183/09031936.00090511
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 regulation of store-operated Ca2+influx in human airway smooth muscle

Abstract: Caveolae, plasma membrane invaginations with constitutive caveolin proteins, harbour proteins involved in intracellular calcium ([Ca2+]i) regulation. In human airway smooth muscle (ASM), store-operated Ca2+ entry (SOCE) is a key component of [Ca2+]i regulation, and contributes to increased [Ca2+]i in inflammation. SOCE involves proteins Orai1 and stromal interaction molecule (STIM)1. We investigated the link between caveolae, SOCE and inflammation in ASM. [Ca2+]i was measured in human ASM cells using fura-2. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 38 publications
1
89
0
Order By: Relevance
“…These data suggest that both channel assemblies are likely to involve lipid raft domains, with TRPC1-STIM1 channel assembly occurring in caveolar microdomains and Orai1-STIM1 association likely in non-caveolar raft microdomains. Although Cav1 was recently shown to affect Orai1 trafficking (Sathish et al, 2012;Yu et al, 2010), we did not find evidence of any alteration in STIM1-Orai1 interaction in Cav1 2/2 cells. We suggest that Orai1-STIM1 channel or other Ca 2+ channels, e.g.…”
Section: Discussionmentioning
confidence: 35%
See 2 more Smart Citations
“…These data suggest that both channel assemblies are likely to involve lipid raft domains, with TRPC1-STIM1 channel assembly occurring in caveolar microdomains and Orai1-STIM1 association likely in non-caveolar raft microdomains. Although Cav1 was recently shown to affect Orai1 trafficking (Sathish et al, 2012;Yu et al, 2010), we did not find evidence of any alteration in STIM1-Orai1 interaction in Cav1 2/2 cells. We suggest that Orai1-STIM1 channel or other Ca 2+ channels, e.g.…”
Section: Discussionmentioning
confidence: 35%
“…2C). Although Cav1 was recently shown to affect Orai1 trafficking (Sathish et al, 2012;Yu et al, 2010), our data indicate that Orai1-STIM1 interaction is not affected in Cav1 2/2 acinar cells and could thus account for the residual Ca 2+ influx. Further, channels including other TRPC subtypes could also contribute toward this residual Ca 2+ entry in Cav1 2/2 cells and thus cannot be excluded.…”
Section: Cav1 Controls the Functional Regulation Of Trpc1 In Vivomentioning
confidence: 82%
See 1 more Smart Citation
“…TNF-a has been known to increase agonist-induced [Ca 21 ] i response and contractility in ASM (1,6,22,25). Our recent studies also showed that TNF-a increases SOCE in human ASM cells (11,22). Similarly, IL-13 enhances agonist-induced [Ca 21 ] i responses in human ASM (26), and increases airway contractility in mouse and rat tracheas (27).…”
Section: Clinical Relevancementioning
confidence: 94%
“…Upon sensing SR Ca 21 depletion, STIM1 oligomerizes with adjacent STIM1 proteins via the SAM domain, and moves within the SR membrane to enhance its proximity to the PM, where STIM1 interacts with Orai1 and transient receptor potential cation channels to form clusters, thus activating these PM channels to induce SOCE (24). Although much of the information on STIM1 was derived from nonexcitable cells and expression systems, STIM1 has been demonstrated in human ASM cells, and is implicated in the regulation of [Ca 21 ] i responses (11,21,22). The knockdown of STIM1 results in reduced SOCE after store depletion, whereas the overexpression of STIM1 dramatically increases SOCE in human ASM cells (21).…”
mentioning
confidence: 99%